2014
DOI: 10.1016/j.ejenta.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Audiological and otological outcome in Bi-island chondroperichondrial graft type I tympanoplasty

Abstract: Background: The principal aims of a tympanoplasty operation are to create an intact tympanic membrane and to restore an optimal hearing improvement. Many surgeons have used cartilage for grafting due to its increased stability and resistance to negative pressure. Cartilage has been criticized because of concerns regarding hearing results.Objectives: The aim of this study is to present the experience of using cartilage for grafting central perforations in type I tympanoplasty procedure with some novel modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
4
1
1
Order By: Relevance
“…In this study among 36 patients 21 (58.3%) were male and 15 (41.7%) were female with male: female ratio of 1.4:1, that is consistent with results of Subramania2 with 42 (52.55%) males, 38(47.5%) female and male: female ratio of 1.1:1, and Dhanapala with 57 (57%) males, 43(43%) female and male: female ratio of 1.3:1 11. However this study results regarding gender distribution differs from Vaishali, Hasaballah and Gupta having female predominance as female 55% male 45%, females 66.6% males 33.4% and females 70% males 30% respectively 3,5,12. In current study mean ± SD age was 27.14 ± 7.49 years, with age range 15 – 50 years and patients presented commonly in 3 rd and 4 th decade of life i.e.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In this study among 36 patients 21 (58.3%) were male and 15 (41.7%) were female with male: female ratio of 1.4:1, that is consistent with results of Subramania2 with 42 (52.55%) males, 38(47.5%) female and male: female ratio of 1.1:1, and Dhanapala with 57 (57%) males, 43(43%) female and male: female ratio of 1.3:1 11. However this study results regarding gender distribution differs from Vaishali, Hasaballah and Gupta having female predominance as female 55% male 45%, females 66.6% males 33.4% and females 70% males 30% respectively 3,5,12. In current study mean ± SD age was 27.14 ± 7.49 years, with age range 15 – 50 years and patients presented commonly in 3 rd and 4 th decade of life i.e.…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly in Pareek’s study mean ± SD age of the patient was 26.23 ± 12.46 years with age range of 10 to 60 years 13. Hasaballah observed that mean ± SD age was 24.9 ± 9.5 years with age range 15–51 years 12. Vaishali also reported that mean age of patients was 29.12 years (range, 15–45 years) and majority of patients (40%) were in 3 rd decade of life 3.…”
Section: Discussionmentioning
confidence: 92%
“…11 However this study results regarding gender distribution differs from Vaishali, Hasaballah and Gupta having female predominance as female 55% male 45%, females 66.6% males 33.4%, and females 70% males 30% respectively. 12 In current study age range was 15-53 years and patients presented commonly in 2 nd and 3 rd decade of life i.e. 79 (47%).…”
Section: Resultsmentioning
confidence: 57%
“…This type of graft feeds by diffusion from the surrounding tissue such as the perichondrium and tympanic-meatal flap and is easily integrated into the tympanic membrane due to its flexibility. Its rigid character makes it robust and resistant to resorption and retraction under prolonged pressure [7][8][9][10]. This resistance is more marked when the cartilage is grafted with its perichondrium [9,10].…”
Section: Discussionmentioning
confidence: 99%